2015
DOI: 10.1016/j.phytochem.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoids and flavonoids from Phlomis kurdica as inhibitors of human lactate dehydrogenase

Abstract: Two new flavonoids, jaceosidin 7-O-β-D-glucopyranosyl-(1→2)-β-D-glucopyranoside (1) and hispidulin 7-O-β-D-glucopyranosyl-(1→2)-β-D-glucopyranoside (2), and one new phenylpropanoid, 3,3′-dimethyl-lunariifolioside (3), along with 11 known compounds (4–14), were isolated from the aerial parts of Phlomis kurdica growing in Jordan. Structures of 1–3 were elucidated on the basis of spectroscopic data. These isolated compounds were assayed for their inhibitory activity against isoform 5 of human lactate dehydrogenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…After challenging the colon tissue with LPS, we observed that both P. fruticosa and P. herba‐venti extracts were able to blunt the increased levels of LDH (Figure ). The inhibitory effect exerted by both extracts on LDH activity is consistent with their content in total flavonoids (Bader et al, ). Additionally, Xianchu, Lan, Ming, and Yanzhi () reported the efficacy of rutin in reducing LDH level in mice challenged with LPS.…”
Section: Resultssupporting
confidence: 67%
“…After challenging the colon tissue with LPS, we observed that both P. fruticosa and P. herba‐venti extracts were able to blunt the increased levels of LDH (Figure ). The inhibitory effect exerted by both extracts on LDH activity is consistent with their content in total flavonoids (Bader et al, ). Additionally, Xianchu, Lan, Ming, and Yanzhi () reported the efficacy of rutin in reducing LDH level in mice challenged with LPS.…”
Section: Resultssupporting
confidence: 67%
“…, benzyl alcohol glycosides (caffeoylquinic acid derivatives), fatty acids and aliphatic compounds (9,12octadecadienoic acid methyl ester and hexadecanoic acid methyl ester), and neolignan glucoside (dehyrodiconiferyl alcohol-4-O-β-D-glucopyranoside) were also reported in previous researches from Phlomis species using 1D and 2D-NMR, FAB-MS, RP-HPLC, GC-MS and HPLC-DAD (Calis et al, 1990;Takeda et al, 2001;Valant-Vetschera et al, 2003;Saracoglu et al, 2003;Harput et al, 2006;Yalcin et al, 2006;Zhang and Wong, 2008;Hussain et al, 2010;Zardoost and Gheibi, 2011;Ullah et al, 2013;Sarikurkcu et al, 2014;Bader et al, 2015;Delnavazi et al, 2016;Zafari-Shayan et al, 2016;Proestos and Varzakas, 2017). Based on different chemical contents, the genus Phlomis was divided into different chemotypes (Amor et al, 2009).…”
Section: Introductionmentioning
confidence: 55%
“…The purity of the flavonoid compounds was carried out by the TLC system. The chromatogram was treated with three systems: methanol-water (15:5), chloroform-methanol (15:5), and acetic acid 15% representing a developing solvent system (Harput et al, 2006;Bader et al, 2015). Spots detection with natural product identifiers (diphenylboric acid 2-aminoethyl ester; Sigma Chemical; in methanol, followed by 5% solution of polyethylene glycol 400 in ethanol) was proved under ultraviolet-366 nm (Figueirinha et al, 2008).…”
Section: Chromatography Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a part of our research program for characterization of the biological activity of different classes of natural products [9,10], herein we report the isolation and the structure characterization of four new phenylethanoid glycosides (1-4) (▶ Fig. 1), along with three known compounds from C. phelypaea aerial parts.…”
Section: New Phenylethanoid Glycosides From Cistanche Phelypaea and Tmentioning
confidence: 99%